THE SPEECH ACT - Martinez del Castillo, Jesus (European Scientific Journal, ESJ, 2014)
Language is nothing but human subjects in as much as they speak,say and know. Language is something coming from the inside of thespeaking subject manifest in the intentional meaningful purpose of theindividual speaker. A language, on the contrary, is something coming fromthe outside, from the speech community, something offered to the speakingsubject from the tradition in the technique of speaking. The speech act is theperformance of an intuition by the subject, both individual and social. It isindividual since it is creation. It is social since it is executed using theparameters and means offered to the speaker by the speech community.Human subjects speak because they have something to say. They saybecause they define themselves before the circumstance they are in. This isso because speakers are able to know. The speech act is nothing but an act ofknowing. Language is born when it is executed in the speech act.